Facilitators and barriers to the delivery of palliative care to patients with Parkinson's disease: a qualitative study of the perceptions and experiences of stakeholders using the socio-ecological model - Yiping Chen; Ru Zhang; Yan Lou; Wei Li; Hui Yang (BMC, 2023)
Abstract Objective Palliative care (PC) can improve the quality of life of Parkinson's disease (PD) patients and their carers. However, the impact of PC services on patients with PD remains unclear. This research was conducted to identify the barriers and facilitators influencing PC services for patients with PD based on the Social Ecological Model (SEM) framework. Methods This research was conducted through semi-structured interviews, employing SEM to organize themes and identify potential solutions across multiple levels. Results A total of 29 interviewees (5 PD clinicians, 7 PD registered nurses, 8 patients, 5 caregivers, and 4 policy makers) completed the interviews. Facilitators and barriers were identified according to the levels of the SEM. Several facilitators were identified, i.e., (1) individual level: the critical needs among PD patients and their relatives and the desire for PC knowledge among health professionals; (2) interpersonal level: social support; (3) organizational level: the investments towards systematization of PC; and nurses are the bridge between patients and doctors; (4) community level: the convenience of community services; and hospital-community-family-based services; (5) culture and policy level: existing policy. Conclusion The social-ecological model proposed in this study helps illuminate the complex and multilevel factors that may influence PC delivery to PD patients.